Corporate governance mechanisms and firm performance in Saudi Arabia before and during the COVID-19 outbreak - Helmi A. Boshnak; Mohammad Alsharif; Majed Alharthi (Cogent Business & Management, 2023)
AbstractThis study examines the impact of corporate governance mechanisms on the performance of listed firms in Saudi Arabia before and during the coronavirus disease (COVID-19) pandemic. The study applied univariate, bivariate, and multivariate analyses to data collected from 258 annual reports from 2019 to 2020. The results show that during the COVID-19 pandemic, firm market performance (Tobin’s Q ratio) has decreased with larger board size, more board meetings, while it has increased with board experience, board education, and board gender (number of women on the board). Moreover, during the COVID-19 pandemic, board gender was found to have a significant positive impact on the firm’s operational performance (return on assets), implying that gender diversity on boards plays a crucial role in times of crisis. The findings have significant implications for Saudi Arabian firms, managers, investors, and policymakers. Furthermore, the latest corporate governance regulations in Saudi Arabia are almost certain to have a significant impact on firm performance, particularly during times of crisis. In addition, corporate governance regulations should consider the importance of small board size, lower board independence, board member experience and education, and board gender diversity to improve corporate performance, especially in times of crisis. Governments and regulators should collaborate to reduce the financial and economic impact of the COVID-19 pandemic. Comprehensive policies are needed to address the negative consequences of current and future crises.